MANAJEMEN LAYANAN BIMBINGAN DAN KONSELING DALAM PENGEMBANGAN KECERDASAN INTRAPERSONAL PESERTA DIDIK: STUDI KUALITATIF DI SMA MUTIARA 2 BANDUNG - Dyah Aryani, Wiwik; Sulastri, Neneng; Amalia, Lia; Sri Patimah, Windary; Wijaya Daerobi, Dendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is not only oriented toward academic achievement but also toward the development of students' personalities, one of which is through the enhancement of intrapersonal intelligence, including self-awareness, emotional regulation, self-recognition, and independent decision-making. However, many students still experience difficulties in these areas, highlighting the need for effective guidance and counseling (GC) service management. This study aims to describe the management of guidance and counseling services in developing students' intrapersonal intelligence at SMA Mutiara 2 Bandung, focusing on the aspects of planning, organizing, implementation, evaluation, as well as the supporting and inhibiting factors affecting its implementation. This study employs a qualitative approach using a descriptive method. Data are collected through observation, in-depth interviews, and documentation involving guidance and counseling teachers, the Vice Principal for Student Affairs, and students. The data are analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data trustworthiness is ensured through triangulation and member checking. The expected outcome of this study is a comprehensive description of the implementation of guidance and counseling service management in supporting the development of students' intrapersonal intelligence, including the factors influencing its effectiveness. This study is expected to contribute theoretically to the development of guidance and counseling management and provide practical recommendations for schools to improve the quality of guidance and counseling services in optimizing students' personal development.